Ways of improving of the system of Higher education in RK (Eurasian Journal of Philology Science and Education, 2016)
The maximum success in modernization of the higher educational system in PK can be achieved in case all program directions of the Government placed into educational policy take all the best possible from positive potential of the US higher educational system in main directions: qualitative selection of school-leavers, qualitative teaching staff, high level of organizing of teaching process, finance provision, development of the infrastructure of the university.
Keywords: high school; the process of restructuring; global priori¬ties; integration into the global educational environment; reforming the national education system